1994
DOI: 10.1177/019459989411000407
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled assessment of the canalith repositioning maneuver

Abstract: The efficacy of the canalith repositioning maneuver in the treatment of benign positional vertigo was assessed in this controlled, randomized trial of 38 subjects. Treated subjects underwent the maneuver and control subjects did not. All were reevaluated 1 month after treatment. The number of persons experiencing subjective improvement was not statistically significantly different between the treatment and control groups. All patients, in both experimental and control groups, in this study experienced substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
3
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 14 publications
2
92
3
1
Order By: Relevance
“…The short-term ( ∼ 1 week after treatment) remission rates in the control group in previous studies ranged from 0 to 25%, which is considerably lower than that of our present study (71-77%) [Amor-Dorado et al, 2012;Chen et al, 2012;Mandala et al, 2012;Soto Varela et al, 2001;von Brevern et al, 2006]. The resolution rate of positional vertigo in untreated patients with posterior canal BPPV could be up to 48% at 1 week and up to 86.4% in 1 month [Blakley, 1994;Sekine et al, 2006]. It is unclear whether these differences are due to differences in patient populations in terms of the spontaneous remission rates and the performance, types, or numbers of sham maneuvers performed.…”
Section: Discussioncontrasting
confidence: 68%
“…The short-term ( ∼ 1 week after treatment) remission rates in the control group in previous studies ranged from 0 to 25%, which is considerably lower than that of our present study (71-77%) [Amor-Dorado et al, 2012;Chen et al, 2012;Mandala et al, 2012;Soto Varela et al, 2001;von Brevern et al, 2006]. The resolution rate of positional vertigo in untreated patients with posterior canal BPPV could be up to 48% at 1 week and up to 86.4% in 1 month [Blakley, 1994;Sekine et al, 2006]. It is unclear whether these differences are due to differences in patient populations in terms of the spontaneous remission rates and the performance, types, or numbers of sham maneuvers performed.…”
Section: Discussioncontrasting
confidence: 68%
“…These proposals varies from no treatment at all 34 , all the way up to a combination of the numerous existing maneuvers and exercises 32,35,36 . In the elderly population, these maneuvers might have to be modified to gentler and slower movements with neck rotation limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the judgement that repositioning techniques produce a beneficial effect separate from the spontaneous resolution of BPPV is difficult to substantiate [14][15][16][17][18][19]. Controlled clinical studies [20,21] have indicated no significant difference between patients treated with repositioning maneuvers and those untreated by these maneuvers. Nevertheless, such maneuvers are without risk, and may be offered as initial treatment of BPPV.…”
Section: Discussionmentioning
confidence: 99%